Analisis Kesulitan Siswa SMA Terhadap Materi Statistika - Anisah Putri Br Munthe; Rizka Tri Andini; Luhtfia Humayra; Muhammad Rijal Hasan Harahap (Department of Master Program on Mathematics Education Faculty of Teacher Training and Education State Islamic Institute of Lhokseumawe, Indonesia, 2023)
Based on the research objectives that have been set in the introductory section, this study explains